2007
DOI: 10.1007/s00467-006-0355-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of kidney chloride channels in health and disease

Abstract: Chloride channels are expressed along the entire mammalian nephron. They participate in transepithelial chloride transport, cell volume regulation and acidification of intracellular vesicles. Some chloride channels are constitutively active and others are regulated by either second messengers such as cAMP or Ca(++) or secondary to changes in membrane potential. The molecular identities of a number of chloride channels within the kidney are still unknown. Abnormalities in chloride channel expression and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…In agreement with this observation, Xie and Shafer [51] demonstrated that the treatment with cAMP stimulates Cl − secretion via cystic fibrosis transmembrane conductance regulator as well as ENaC-mediated Na + absorption in MDCK cells. This could be in agreement with a lack of a kidney phenotype in cystic fibrosis patients [53], [54], in which CFTR activity is compromised, but chloride intracellular concentration could be modulated by the plethora of chloride channels [55] and transporters [56] that are active in kidney cells.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with this observation, Xie and Shafer [51] demonstrated that the treatment with cAMP stimulates Cl − secretion via cystic fibrosis transmembrane conductance regulator as well as ENaC-mediated Na + absorption in MDCK cells. This could be in agreement with a lack of a kidney phenotype in cystic fibrosis patients [53], [54], in which CFTR activity is compromised, but chloride intracellular concentration could be modulated by the plethora of chloride channels [55] and transporters [56] that are active in kidney cells.…”
Section: Discussionsupporting
confidence: 68%
“…Cl channels are expressed in almost all cells in the body. Dysfunctions in the Cl channel result in a broad spectrum of diseases [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Cellular Cl alterations due to dysfunctions in Cl channels result in a broad spectrum of diseases (Puljak and Kilic, 2006;Veizis and Cotton, 2007;Tang et al, 2010). Thus, conceptually, hyperchloremia caused by saline infusion cannot be viewed as normal.…”
Section: Hyperchloremia and Hyperchloremic Acidosis Are Abnormalmentioning
confidence: 99%